Enhanced chitin gel with magnetic nanofiller for lysozyme purification - Tovar Jimenez, Gabriel Ibrahin (2020)
In this study, we have investigated the impact of superparamagnetic magnetite nanoparticle (Fe3O4) inclusion on the chitin polysaccharide structure, together with its surface chemistry influence on the adsorption of lysozyme (LYZ). Magnetic nanoparticles (MNPs) as fillers not only endow the chitin host structure with their physic and chemical properties but also is a straightforward tool to modify or template its porous structure. Indeed, scanning electron microscopy and Brunauer–Emmett–Teller surface area measurements confirm the template effect of the MNPs on chitin. Their incorporation reduced the thickness of the pore wall and increased the surface area from chitin (34.5 m2/g) to the chitin@Fe3O4 composites (210.8 m2/g). MNPs provide the composite system an intrinsic magnetic moment that enables the magnetic recovery of the adsorbent after LYZ uptake. To characterize the magnetic composite's interaction with LYZ, the effect of pH on the absorptive capacities and kinetic parameters was examined. The results indicated that the nanocomposite presents an adsorption capacity of 488 mg/g of lysozyme at pH 9, being able to recover LYZ without diluting or pretreating the hen egg-white, leading to a 75% global yield and a purity degree >99% in only one chromatographic step.